The Dispositional Essence of Proactive Social Preferences: The Dark Core of Personality vis-à-vis 58 Traits - Hilbig, Benjamin E.; Thielmann, Isabel; Zettler, Ingo; Moshagen, Morten (Psychological Science, 2023)
Individuals differ in how they weigh their own utility versus others’. This tendency codefines the dark factor of personality (D), which is conceptualized as the underlying disposition from which all socially and ethically aversive (dark) traits arise as specific, flavored manifestations. We scrutinize this unique theoretical notion by testing, for a broad set of 58 different traits and related constructs, whether any predict how individuals weigh their own versus others’ utility in proactive allocation decisions (i.e., social value orientations) beyond D. These traits and constructs range from broad dimensions (e.g., agreeableness), to aversive traits (e.g., sadism) and beliefs (e.g., normlessness), to prosocial tendencies (e.g., compassion). In a large-scale longitudinal study involving the assessment of consequential choices (median N = 2,270; a heterogeneous adult community sample from Germany), results from several hundred latent model comparisons revealed that no meaningful incremental variance was explained beyond D. Thus, D alone is sufficient to represent the social preferences inherent in socially and ethically aversive personality traits.